2019
DOI: 10.4149/bll_2019_036
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor effects of lidocaine on human gastric cancer cells in vitro

L Ye1,
et al.

Abstract: Currently, there exists an urgent need to investigate the anti-cancer effects of lidocaine on gastric cancer cells. The purpose of the present study was to evaluate the anti-tumor effects and the underlying mechanisms of lidocaine in gastric cancer cells. Our results indicated that lidocaine signifi cantly suppressed proliferation, migration and invasion and induced apoptosis in a dose-dependently manner in human gastric cancer cells. In addition, our data shown that the expression of Bcl-2 was decreased and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…Intravenous lidocaine injections may effectively relieve pain and reduce fentanyl consumption during the early postoperative period (28). Recent studies have demonstrated a possible regulatory mechanism of action for lidocaine through suppressing the proliferation of gastric cancer cells, which is associated with ERK1/2 phosphorylation, the MAPK pathway and altering the expression profiles of microRNAs (3)(4)(5). EMT activation is involved in the cell invasion and metastasis of a variety of cancer types (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenous lidocaine injections may effectively relieve pain and reduce fentanyl consumption during the early postoperative period (28). Recent studies have demonstrated a possible regulatory mechanism of action for lidocaine through suppressing the proliferation of gastric cancer cells, which is associated with ERK1/2 phosphorylation, the MAPK pathway and altering the expression profiles of microRNAs (3)(4)(5). EMT activation is involved in the cell invasion and metastasis of a variety of cancer types (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine is a local anesthetic which can effectively inhibit the biological activity of a variety of cancer types. In vivo and in vitro studies have indicated the antitumor effects of lidocaine in gastric cancer (3)(4)(5). Mechanistically, lidocaine has been found to decrease Src activation (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…As summarized in Table 1 and Figure 2 , the reported targets/mechanisms include MMP-9 ( Piegeler et al, 2015 ), ERK ( Chen et al, 2019 ), TRPV6 ( Jiang et al, 2016 ), and VEGF/VEGFR2 ( Gao et al, 2019 ), as well as the regulation of epigenetics ( Li et al, 2014 ), mi-RNA ( Qu et al, 2018 ; Sui et al, 2019 ; Yang Q. et al, 2019 ), inhibition of metastasis ( D’Agostino et al, 2018 ; Johnson et al, 2018 ; Sun and Sun, 2019 ), inhibition of inflammation ( Freeman et al, 2019 ), impacting mitochondrial metabolism ( Okamoto et al, 2017 ; Gong et al, 2018 ), the regulation of reactive oxygen species (ROS) ( Okamoto et al, 2016 ), etc. Importantly, as an ion channel regulator, lidocaine may exert its anticancer effects via regulation of other channels or membrane potential, such as mitochondrial membrane potential (MMP), which may lead to the decrease of MMP, finally resulting in the mitochondria-related apoptosis ( Li et al, 2014 ; Lu et al, 2016 ; Ye L. et al, 2019 ), providing valuable information for its targets identification. However, further studies are warranted to confirm its exact targets in different cancer types.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Another study conducted on human gastric cancer SGC7901 and BGC823 cells, lidocaine inhibited their proliferation, migration, and invasion and induced apoptosis in a concentration- (0.1–10 Mm, determined by MTT) and time- (0–72 h) dependent manner. Mechanistic studies showed that lidocaine increased the Bax/Bcl-2 ratio, increased the anti-apoptotic p-p38, and altered the MAPK expression, suggesting a mitochondria-mediated apoptosis pathway ( Ye L. et al, 2019 ).…”
Section: Lidocaine In Cancer Treatmentmentioning
confidence: 99%
“…Local anesthetic used during the operation benefits cancer patients with breast cancer, common cancer and gastric cancer through suppressing the metastasis and recurrence of tumors [ 22 , 23 ]. Bupivacaine is one of the amide-linked local anesthetics.…”
Section: Discussionmentioning
confidence: 99%